O-034 Correlation between angiographic stenosis and physiologic venous sinus outflow obstruction in idiopathic intracranial hypertension. (22nd July 2018) - Greeneway, G; West, J; Garner, R; Aschenbrenner, C; Singh, J; Wolfe, S; Fargen, K
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) with associated venous sinus stenosis (VSS) can be successfully treated with stenting. The relationship between degree of angiographic sinus stenosis and the trans-stenosis pressure gradient magnitude is poorly understood. The present study aimed to assess the utility of angiography, venography, and magnetic resonance venography (MRV) for the diagnosis and characterization of clinically significant VSS. Methods: A retrospective analysis was performed of a prospectively collected database of patients with medically refractory IIH who were evaluated by angiography and venous manometry for the presence of VSS with associated clinically significant pressure gradient (defined as ≤8 mmHg or as 6–7 mmHg in select cases). Angiographic stenosis was measured using novel methodology in both venous phase arteriography and venography by two independent raters. Results: Thirty-seven patients met inclusion criteria for the study. Eighty-nine percent were women and the average age was 33.8 years. In total, 70% of patients had clinically significant pressure gradients and were selected for stenting. The optimal percentage stenosis for detection of a significant pressure gradient was 34% stenosis on venous phase arteriography (sensitivity 0.81 and specificity 0.91) and 31% stenosis on venography (0.92 and 0.73). For every 10% increase in stenosis, an approximate increase in pressure gradient of 3.5 mmHg is seen. MRV/CTV had a calculated sensitivity of 0.42, a specificity of 1.0, and a negative predictive value of 22% for identifying a significant pressure gradient. Conclusion: The degree of stenosis predictive of a clinically significant pressure gradient (30%–35%) in the venous sinuses is considerably lower than the arterial stenosis at which pathologic hemodynamic alterations occur. Physiologic measurement of the pressure gradient associated with stenosis remains the most important evaluation to determine the clinical significance of cerebral VSS. MRV does not appear to be a suitable diagnostic evaluation for the purposes of ruling out clinically significant cerebral VSS. For both arteriogram (panel A) as well as venogram (panel B), stenosis as measured by each independent rater is plotted and clinically significant pressure gradients are shown in color, highlighting the diagnostic characteristics of the statistically-determined optimum cut-point for stenosis. The receiver operating characteristic curves for both arteriogram (red) and venogram (blue) are shown in panel C. Disclosures: G. Greeneway: None. J. West: None. R. Garner: None. C. Aschenbrenner: None. J. Singh: None. S. Wolfe: None. K. Fargen: None.